Ultrafast many-body dynamics in an ultracold Rydberg-excited atomic mott insulator - Bharti, Vineet; Sugawa, S.; Mizoguchi, M.; Kunimi, M.; Zhang, Y.; de Léséleuc, S.; Tomita, T.; Franz, Titus; Weidemüller, Matthias; Ohmori, K. (Arxiv, 2022)
We report the observation and control of ultrafast non-equilibrium many-body electron dynamics in Rydberg-excited spatially-ordered ultracold atoms created from a three-dimensional unity-filling atomic Mott insulator. By implementing time-domain Ramsey interferometry with attosecond precision in our Rydberg atomic system, we observe picosecond-scale ultrafast many-body dynamics that is essentially governed by the emergence and evolution of many-body correlations between long-range interacting atoms in an optical lattice. We analyze our observations with different theoretical approaches and find that quantum fluctuations have to be included beyond semi-classical descriptions to describe the observed dynamics. Our Rydberg lattice platform combined with an ultrafast approach, which is robust against environmental noises, opens the door for simulating strongly-correlated electron dynamics by long-range van der Waals interaction and resonant dipole-dipole interaction to the charge-overlapping regime in synthetic ultracold atomic crystals.
Gesehen am 10.01.2024